I have a questions about propogation of error.
I have two variables that are used to calculate the total value.
C = A * B
A = X * Y
B = Z / Y
So when substituting A and B to calculate C, the Y cancels and I am left with C = X * Z
But what if I know the total uncertainty of X, Y, and Z and I would like to calculate the uncertainty of C?
I am aware it must be done with:
But would this mean that: ??
Or would the Y cancel out even in the uncertainty calculation leaving: ??
Thanks for any help you guys can offer!